Risk of recurrent cardiovascular events in coronary artery disease patients with Type D personality - Torgersen, Kristin Stensland; Sverre, Elise Christine Bjørkholen; Weedon-Fekjær, Harald; Andreassen, Ole A.; Munkhaugen, John; Dammen, Toril (Frontiers in Psychology, 2023)
Data on the association between Type D personality, its traits negative affectivity (NA) and social inhibition (SI), and risk of major adverse cardiac events (MACE) in coronary outpatients is sparse. Furthermore, the associations between Type D subgroups and cardiovascular risk factors are largely unknown. We investigated i) Type D personality, NA and SI and risk of recurrent MACE, and ii) the relationship between Type D subgroups and risk factors in a coronary population. This prospective cohort study included 1083 patients` median 16 months after a myocardial infarction and/or a revascularization procedure who were followed-up for 4.2 (SD 0.4) years. Type D personality was assessed by DS14. Anxiety and depression, statin adherence, and risk factors were assessed by patients’ self-report and a clinical examination with blood samples. MACE, defined as cardiovascular death, myocardial infarction, revascularization, stroke or heart failure, were obtained from hospital records from index event to end of study lasting 5.7 years. Data were analyzed by Cox proportional hazard regression. In all, 352 MACE occurred in 230 patients after average 4.2 years follow-up. Higher NA score was associated with MACE after adjustment for age, risk factors and comorbidity (HR 1.02 per unit increase, 95% CI 1.00-1.05), whereas we found a weaker, not statistically significant estimated effect of higher SI score. After additional adjustment for symptoms of anxiety and depression, we found a weaker, not statistically significant association between NA and MACE (HR 1.01 per unit increase, 95% CI 0.98-1.05). Low statin adherence and smoking were more prevalent in the Type D and high NA group. Our results indicate that the NA trait is related to worse prognosis in outpatients with coronary artery disease.